2012
DOI: 10.1111/j.1526-4637.2012.01296.x
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 Poor Metabolizer Genotype and Smoking Predict Severe Postoperative Pain in Female Patients on Arrival to the Recovery Room

Abstract: This study demonstrated that female patients possessing the PM genotype of CYP2D6 and patients who smoke had a higher incidence of acute severe postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Most researchers have reported no significant difference in incidence of PONV between EMs and PMs (Candiotti et al, 2005; Janicki, Schuler, Jarzembowski, & Rossi, 2006). In one recent study, however, Yang and colleagues (2012) reported the occurrence of severe postoperative pain was significantly higher in PMs as compared to the other metabolizer groups, requiring higher doses of opioids for pain relief.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Most researchers have reported no significant difference in incidence of PONV between EMs and PMs (Candiotti et al, 2005; Janicki, Schuler, Jarzembowski, & Rossi, 2006). In one recent study, however, Yang and colleagues (2012) reported the occurrence of severe postoperative pain was significantly higher in PMs as compared to the other metabolizer groups, requiring higher doses of opioids for pain relief.…”
Section: Discussionmentioning
confidence: 90%
“…Ultrametabolizers (UMs) are the result of a copy number variant (extra genes), resulting in increased metabolic capacity (Arneth et al, 2009). UMs usually require less opioids in the postoperative period compared to the other groups due to enhanced metabolic activity (Yang, et al, 2012), yet they are also at risk of intense adverse events from this more rapid metabolism (Leppert, 2011). …”
mentioning
confidence: 99%
“…For opioid metabolism, the relationship of pain and polymorphisms of cytochrome P450 enzymes (CYP2D6, CYP2B6, and CYP3A4) are well documented [83]. In a study by Yang et al [84], 71 % of postoperative patients with acute severe pain had the CYP2D6 poor metabolizer genotype. In a separate analysis, ultrametabolizers for CYP2D6 also demonstrated higher efficiency in synthesizing endogenous morphine compared to other CYP metabolizer groups and required significantly less morphine in the postoperative period [85].…”
Section: Genetics Of Cpspmentioning
confidence: 99%
“…5 Estudos enfatizaram que o tabagismo é um dos preditivos de dor intensa no período pós-operatório. 18 Em outro estudo, no qual 520 extrações dentárias foram feitas, o tabagismo foi relatado entre os fatores relacionados ao aumento dos níveis de dor após a extração do dente. 19 Em fumantes, privados de nicotina no período pós-operatório, houve um aumento da necessidade de opiáceos para analgesia controlada pelo paciente.…”
Section: Discussionunclassified